Quality by Design-Guided Systematic Development and Optimization of Mucoadhesive Buccal Films - Alharith A. A. Hassan; Katalin Kristó; Yousif H.-E. Y. Ibrahim; Géza Regdon; Tamás Sovány (MDPI AG, 2023)
Mucoadhesive buccal films have found increased popularity in pharmaceutical drug delivery due to the several advantages that they possess. The present study strives to develop and optimize chitosan-based mucoadhesive buccal films by relying on quality-by-design (QbD) principles. Previous knowledge and experience were employed to firstly identify the critical quality attributes (CQAs), followed by a thorough risk assessment, which led to the selection of seven critical material attributes and process parameters, namely, the polymer grade and concentration, the plasticizer type and concentration, the citric acid (CA) concentration, the amount of the casted solution, and the drying condition. Their effects on the breaking hardness and mucoadhesivity, selected as CQAs, were investigated in three steps by three designs of the experiment (DoE). The medium molecular weight of chitosan (CH) was the preferred choice in the optimized formulation, and its concentration was the most important factor affecting the CQAs, thickness, and moisture content of the films. It was found that 0.364 g/cm2 was the suitable amount of the casting solution, and its optimum drying conditions were presented in the form of a design space. Glycerol (Gly) was the best choice as a plasticizer, and a design space representing several combinations of CH and CA concentrations that produce films with the required quality was constructed at a fixed concentration of 35% Gly. A formula from this design space was selected and employed to load with two model drugs to test its drug-carrying properties for drugs with different physicochemical characteristics. Uniform drug distribution with an immediate release profile was achieved in both drugs, although one of the CQAs was outside of the specifications in the case of lidocaine-containing film. To summarize, the obtention of the optimum mucoadhesive buccal film based on CH was efficiently facilitated by the rational application of QbD principles and the DoE approach.